An efficient multiphase bioprocess for enhancing the renewable energy production from almond shells. (1st January 2020) - Kaur, Manpreet; Kumar, Manoj; Sachdeva, Sarita; Puri, S.K.
Graphical abstract: Highlights: A novel biorefinery approach was explored to produce hythane from ethanol stillage. Ideal hythane ratio of 0.29 was successfully obtained in two-stage AD of stillage. Higher carbon conversion efficiency (75%) validated the efficacy of integration. Energy analysis (EROI) assured the practical feasibility of the proposed method. Biochar produced from digested almond shells exhibited agronomic properties. Abstract: The present study is based on "waste to energy" concept, wherein the potential of almond crop residues viz ., almond shells were investigated for biofuel production via different bioprocesses. Three routes, namely A1 representing hythane production through two-stage anaerobic digestion (TSAD), A2 representing ethanolic fermentation and A3 representing coupled ethanol and hythane production were evaluated for maximizing energy recovery. Results showed that in route A1, increased H2 /(H2  + CH4 ) ratio (0.53) resulted in inappropriate hythane composition which was attributed to higher hydrogen yield of 236.6 L/kg chemical oxygen demand removed (CODr ) and lower methane production (203.9 L/kg CODr ) in the respective route. In route A2, sole ethanol production led to much lower carbon conversion efficiency (25.7%) and energy yield (6173.1 kJ/kg CODr ) that questions the feasibility and efficiency of this process. However, in route A3, coupled ethanol and hythane production led to increased substrate degradation (91.3%) and higher carbon conversion efficiency (75.1%) resulting in enhanced energy recovery (22156.6 kJ/kg CODr ) as compared to A1 route (13573.6 kJ/kg CODr ). The stable H2 /(H2  + CH4 ) ratio of 0.29 obtained in route A3 makes this pathway most suitable for efficient co-production of both biofuels. Further, linking of biochemical conversion process with thermochemical process viz ., pyrolysis to produce biochar from almond shell residue, could be seen as an effective strategy for waste management and for enhancing the economic viability of the process.